METHODS OF SOFTWARE QUALITY MANAGEMENT - KUSTOVSKYI, ROMAN; YASHYNA, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents methods of software quality management. Software quality is defined as the extent to which a software product meets the requirements and needs of its users. It refers to both the software itself and the processes of its creation. Well-made software is characterised by being sufficiently free from errors and defects, delivered on time and on budget, and meeting requirements and being maintainable. Structured software quality management is about software quality assurance (SQA), planning (SQP) and control (SQC). the way to create high-quality software is to implement effective quality management with an appropriate methodology. After the above steps, testing is the main activity that identifies and resolves technical problems in the software source code, evaluates the overall usability, performance, security and compatibility of the product. Software quality assurance is its prevention, which involves the creation of instructions, implementation of standards, and improvement of processes throughout the software life cycle to ensure that the quality criteria are met. Planning, in turn, deals with setting standards, instructions, ensuring their inclusion in project planning by creating a quality plan, which often contains a description of quality control activities with the definition of time, performers, methods and resources. Among the methods of improving the software testing process and improving the quality of software products are: planning the testing and quality control process, using test-oriented software development management, conducting formal technical reviews, providing an appropriate working environment for the team, implementing user acceptance testing (UAT), optimising the use of automated tests, implementing exploratory and ad hoc testing, using measurement, and so on. The proposed methods can be applied to software quality monitoring and management. The presented methodology suggests that for effective software quality management it is necessary to cover all its key aspects, such as effective planning, a test-oriented approach to quality management and a specially formed professional team.